Emerging roles for antigen presentation in establishing host–microbiome symbiosis. Issue 1 (July 2016) - Bessman, Nicholas J.; Sonnenberg, Gregory F.
Summary: Trillions of beneficial bacteria inhabit the intestinal tract of healthy mammals from birth. Accordingly, mammalian hosts have evolved a series of complementary and redundant pathways to limit pathologic immune responses against these bacteria, while simultaneously protecting against enteric pathogen invasion. These pathways can be generically responsive to the presence of any commensal bacteria and innate in nature, as for IL‐22‐related pathways. Alternatively, specific bacterial antigens can drive a distinct set of adaptive immune cell responses, including IgA affinity maturation and secretion, and a recently described pathway of intestinal selection whereby MHCII + ILC3 deletes commensal bacteria‐reactive CD4 T cells. These pathways can either promote or inhibit colonization by specific subsets of commensal bacteria, and cooperatively maintain intestinal homeostasis. In this review, we will highlight recent developments in understanding how these diverse pathways complement each other to cooperatively shape the symbiotic relationship between commensal bacteria and mammalian hosts.